2006
DOI: 10.1016/j.jtcvs.2006.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection in the failing heart: I. Effect of cardioplegia and the beating state under simulated left ventricular restoration

Abstract: Coronary blood flow alterations occurred only in failing hearts when geometry was changed from closed to open state. The beating method provided more endocardial flow than cardioplegic delivery during ventricular exposure for restoration. Vascular remodeling raised coronary vascular resistance in failing hearts, thereby requiring higher pressure for similar blood flows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Helmer et al (6) indicated that the LV free wall received less blood flow with an increased flow resistance than the septum during 21-28 days of ventricular pacing. We found that the 3-to 4-wk ventricular pacing increased the vascular flow resistance by ϳ100% in an open heart procedure in situ perfused by nonpulsatile cardioplegia (16,18). The ex vivo measurements indicated ϳ75% increase in vascular flow resistance of the LV free wall (i.e., 1.2 Ϯ 0.11 mmHg·min·ml Ϫ1 in control vs. 2.1 Ϯ 0.15 mmHg·min·ml Ϫ1 in CHF, while the computational results were within Ϯ1 SD of the measurements), which was less than the in situ change likely because of the substantial lack of vasomotor tone in the ex vivo measurement.…”
Section: Structural and Functional Coronary Remodelingmentioning
confidence: 88%
See 2 more Smart Citations
“…Helmer et al (6) indicated that the LV free wall received less blood flow with an increased flow resistance than the septum during 21-28 days of ventricular pacing. We found that the 3-to 4-wk ventricular pacing increased the vascular flow resistance by ϳ100% in an open heart procedure in situ perfused by nonpulsatile cardioplegia (16,18). The ex vivo measurements indicated ϳ75% increase in vascular flow resistance of the LV free wall (i.e., 1.2 Ϯ 0.11 mmHg·min·ml Ϫ1 in control vs. 2.1 Ϯ 0.15 mmHg·min·ml Ϫ1 in CHF, while the computational results were within Ϯ1 SD of the measurements), which was less than the in situ change likely because of the substantial lack of vasomotor tone in the ex vivo measurement.…”
Section: Structural and Functional Coronary Remodelingmentioning
confidence: 88%
“…The chest was closed, and the animal was allowed to recover from the surgery for 1 wk. Ventricular pacing was then initiated at 210 -220 beats/min for 1 wk, and 190 -220 beats/min for additional 2-3 wk, depending on the status of the heart (16,18).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular remodeling raises the coronary vascular resistance in the failing heart, thereby requiring higher pressure for similar blood flow. 16 For the SAVE operation under a beating heart, the LV is opened from the apex to the base along to the left anterior descending artery. Although kinesis of the LV wall is examined preoperatively, palpation of the LV muscle during its contraction allows differentiation of akinetic and normal muscle.…”
Section: Left Ventricular (Lv) Restoration and Ischemic Cardiomyopathmentioning
confidence: 99%
“…After the SAVE operation, 16 the conical shape is restored by inserting an oblique patch between the apex and high septum, just below the aortic valve, with subsequent closure of the excluded wall over the patch. It has been proposed that successful surgical LV restoration should restore normal helical myofiber orientation.…”
Section: Left Ventricular (Lv) Restoration and Ischemic Cardiomyopathmentioning
confidence: 99%